2003
DOI: 10.1074/jbc.m308317200
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of PTIO and Carboxy-PTIO with ·NO, ·NO2, andO2.¯

Abstract: Nitronyl nitroxides, such as derivatives of 2-phenyl-4,4,5,5,-tetramethylimidazoline-1-oxyl 3-oxide (PTIOs), react with ⅐ NO to form the corresponding imino nitroxides (PTIs) and ⅐ NO 2 . PTIOs are considered as monitors of ⅐ NO, stoichiometric sources of ⅐ NO 2 , biochemical and physiological effectors, specific tools for the elimination of ⅐ NO, and potential therapeutic agents. However, a better understanding of the chemical properties of PTIOs, especially following their reaction with ⅐ NO, is necessary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 41 publications
(40 reference statements)
8
126
1
Order By: Relevance
“…To evaluate the importance of NO in the observed relaxation effects (Figs 3 and 4), the NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) was applied [39]. cPTIO (100 μM) alone had no effect on basal vascular tone, but significantly increased contraction in the presence of phenylephrine ( Fig.…”
Section: Modulation Of the Relaxation Effect Of The 'Ssno -Mix' And Gsnomentioning
confidence: 99%
“…To evaluate the importance of NO in the observed relaxation effects (Figs 3 and 4), the NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) was applied [39]. cPTIO (100 μM) alone had no effect on basal vascular tone, but significantly increased contraction in the presence of phenylephrine ( Fig.…”
Section: Modulation Of the Relaxation Effect Of The 'Ssno -Mix' And Gsnomentioning
confidence: 99%
“…N. multiformis was cultivated in 20 ml phosphate-buffered mineral medium (Skinner and Walker, 1961) amended with 1 mM NH 4 Cl and pH was adjusted regularly with 5% Na 2 CO 3 . In early to mid-exponential phase of growth, 150 μM of 2-phenyl-4,4,5,5,-tetramethylimidazoline-1-oxyl 3-oxide (PTIO; Sigma-Aldrich, Vienna, Austria), a chemical that scavenges NO (Goldstein et al, 2003) was injected into the cultures. Ammonium consumption and nitrite production were measured over a period of 6-8 days using standard colorimetric assays (Clesceri et al, 1998) and N 2 O was measured via GC (AGILENT 6890N, Vienna, Austria; injector: 120°C, detector: 350°C, oven: 35°C, carrier gas: N 2 ) in connection with an automatic sample-injection system (DANI HSS 86.50, Head-space-Sampler, Sprockhövel, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To examine if NO 2 radical is an important intermediate in the reaction mechanism, we examined the effect of CPTIO. Goldstein and co-workers (21) have recently shown that the nitronyl nitroxide CPTIO reacts with NO 2 with a rate constant of 1.5 ϫ 10 7 M Ϫ1 s Ϫ1 yielding nitrite and CPTIO ϩ cation. The reaction is reversible with an equilibrium constant of 145.…”
Section: Effect Of Nitrite and Oxyhb Concentration On Oxidation Kinetmentioning
confidence: 99%